Environmental determinants of previtamin D synthesis in the United Arab Emirates. Issue 1 (1st January 2017) - Buckley, Adam J.; Hannoun, Zara; Lessan, Nader; Holick, Michael F.; Barakat, Maha T.
ABSTRACT: Despite abundant sunshine throughout the year, vitamin D deficiency is endemic in the UAE. Solar radiation within the UVB range of the spectrum is required for the photosynthesis of previtamin D3 in the skin. Atmospheric transmission of UVB is strongly influenced by atmospheric conditions and solar zenith angle. We investigated the effects of diurnal and seasonal variation on the availability of sufficient UVB radiation for adequate previtamin D3 synthesis using an established in vitro model. Borosilicate ampoules of 7-dehydrocholesterol, the precursor of previtamin D3, in ethanol (50 µg/mL) were exposed to direct sunlight in an urban area of Abu Dhabi, at one hourly intervals between 0800 and 1700, on one day of each month over a period of one year. Conversion to previtamin D3, vitamin D3 and metabolically inactive photoisomers was analyzed using high performance liquid chromatography. The efficiency of 7-dehydrocholesterol conversion to previtamin D3 varied estimated UVB intensity. At the latitude of Abu Dhabi (24.2 N) previtamin D3 synthesis can occur throughout the year. However very little if any previtamin D3 was produced before 0900 hrs.and after 1600 hrs. Local conditions in Abu Dhabi are likely sufficient to maintain vitamin D levels throughout the year given adequate sun exposure.